Conditioning and dewatering of anaerobically digested sludge from municipal wastewater treatment processes - Lau, Shiew Wei (Curtin University, 2015)
This thesis presented the dewatering performance improvement of anaerobically digested sludge with novel application and assessment of conditioning aids. The effectiveness of sludge conditioning was evaluated by batch experiments using a series of 250-mL jar test beakers. The optimal dosage was found at 15–20 g/kg chitosan with enhanced dewaterability and rheological behaviour. The dual-chemical conditioning results indicate a higher rate of water removal at the expense of dry solids content compared to single conditioning.